Factors Associated with Uncontrolled Hypertension among Renal Transplant Recipients Attending Nephrology Clinics in Nairobi, Kenya - Mary N. Kubo; Joshua K. Kayima; Anthony J. Were; Seth O. McLigeyo; Elijah N. Ogola (Journal of Transplantation)
Objective. To determine the factors associated with poor blood pressure control among renal transplant recipients in a resource-limited setting. Methods. A cross-sectional study was carried out on renal transplant recipients at the Kenyatta National Hospital. Sociodemographic details, blood pressure, urine albumin : creatinine ratio, and adherence using the MMAS-8 questionnaire were noted. Independent factors associated with uncontrolled hypertension were determined using logistic regression analysis. Results. 85 subjects were evaluated. Mean age was 42.4 (SD ± 12.2) years, with a male : female ratio of 1.9 : 1. Fifty-five patients (64.7%) had uncontrolled hypertension (BP ≥ 130/80 mmHg). On univariate analysis, male sex (OR 3.7, 95% CI 1.4–9.5, p=0.006), higher levels of proteinuria (p=0.042), and nonadherence to antihypertensives (OR 18, 95% CI 5.2–65.7, p<0.001) were associated with uncontrolled hypertension. On logistic regression analysis, male sex (adjusted OR 4.6, 95% CI 1.1–19.0, p=0.034) and nonadherence (adjusted OR 33.8, 95% CI 8.6–73.0, p<0.001) were independently associated with uncontrolled hypertension. Conclusion. Factors associated with poor blood pressure control in this cohort were male sex and nonadherence to antihypertensives. Emphasis on adherence to antihypertensive therapy must be pursued within this population.